Financial Literacy on the Sustainability of Smes in Gowa District - Anwar, Anwar; Serly, Serly (PT. Maju Malaqbi Makkarana, 2022)
This research is a qualitative research that aims to find out how the level of financial literacy affects the sustainability of SMEs in Gowa Regency. The sample in this study consisted of 8 informants from small and medium enterprises. The research data analysis technique uses the help of Atlas.ti 9. The results of the analysis show thatsmall businesses are classified as sufficient literate (62.5%) and medium businesses are classified as well literate (37.5%). Based on the financial literacy of SMEs, it can be concluded that small businesses have potential and medium businesses have great potential for sustainability.